GenomeDelta: detecting recent transposable element invasions without repeat library - Riccardo Pianezza; Anna Haider; Robert Kofler (Genome Biology)
Abstract We present GenomeDelta, a novel tool for identifying sample-specific sequences, such as recent transposable element (TE) invasions, without requiring a repeat library. GenomeDelta compares high-quality assemblies with short-read data to detect sequences absent from the short reads. It is applicable to both model and non-model organisms and can identify recent TE invasions, spatially heterogeneous sequences, viral insertions, and hotizontal gene transfers. GenomeDelta was validated with simulated and real data and used to discover three recent TE invasions in Drosophila melanogaster and a novel TE with geographic variation in Zymoseptoria tritici.